Knowledge Creation and Business Process Re-Engineering Outcomes of Financial Services: Moderating Effect of Knowledge Sharing - Nkurunziza, Gideon; Walugembe, Ahmed; Mpeera Ntayi, Joseph; Obedgiu, Vincent (SEISENSE Journal of Management, 2023)
Purpose - The researcher investigates the extent to which knowledge sharing moderates the relationship between knowledge creation and business process re-engineering (BPR) outcomes of financial services offered by financial institutions in Uganda. Design/Methodology - The study adopted cross-sectional survey design to collect data at one point in time using self-administered questionnaire to examine the relationship between knowledge creation and business processes. The study at first used statistical package for social scientists to establish clusters among the surveyed financial services and later a model was derived using R programming software to test for knowledge creation and business process re-engineering performance outcomes. Findings - The study found a significant conditional effect of knowledge sharing on knowledge creation and business process re-engineering outcomes. Implying that investment in knowledge sharing creates awareness about the financial services outcomes of financial institutions using business process re-engineering to provide financial services. Originality - This study contributes to business process re-engineering literature by advancing the idea that BPR is an important economic resource that enhanced through instituting knowledge creation and sharing practices in a complex environment. Ideally, creating and sharing knowledge is one of the drivers of customer value, efficiency, and effectiveness of financial services in financial institutions. Practical Implications - Managers of financial institutions need to pay keen interest in managing business processes using relevant knowledge and transforming in new products, new processes, and new markets to boost business process re-engineering outcomes by building a strong knowledge creation system through training and development programs for senior managers.